Performance of Purifying Synthetic High-Strength Chemical Fertilizer Wastewater by Earthworm Eco-Filter System - Cheng1, P.; Ge2, Z.G.; Zhao2, Y.J.; Yan3, C.; Hu4, C.W. (Asian Journal of Chemistry, 2013)
Agricultural wastewater pollution has attracted increasing interest over the past decades owing to its significant effects on water quality. The agricultural wastewater coming from chemical fertilizers is a typical high-strength wastewater. The earthworm eco-filter is a potentially useful method for chemical fertilizer wastewater treatment. The performance and temporal variation of four different kinds of earthworm eco-filter systems in response to high carbon and high nitrogen loadings were analyzed in this research. The four kinds of earthworm eco-filter systems all exhibited high nutrient removal efficiencies under various high-strength loading treatments and the optimum earthworm eco-filter system was the earthworm eco-filter system with earthworms and plants. Relatively higher nutrient removal efficiency was achieved in summer (July, August and September) after increasing in spring (March, April and June). However, it decreased quickly during autumn (October and November) and winter (December and January). The best removal effect was obtained in August. The removal efficiencies of chemical oxygen demand, total nitrogen and total phosphorus were only significantly affected (p < 0.05) by season, system variation and their combined effects.